Evaluación de la gestión administrativa y su influencia en la satisfacción laboral de los servidores públicos del GAD del Cantón Tosagua - Falcones Párraga, Karla Yaritza (2022)
The objective of this research was to evaluate the administrative management of the public servants of the Municipal Autonomous Decentralized Government in Tosagua Canton for the improvement of job satisfaction. The methods used were inductive, deductive and analytical that gave scientific support to the work. Likewise, through the field investigation, the extraction of real information was achieved through an interview with the head of the Human Talent department, in addition an observation sheet was applied that served to evaluate the administrative management of the GAD workers, later it was applied a survey to public servants to detect the main shortcomings in the different administrative areas. The results obtained showed that 66% of employees received training for professional updating, 36% said that there is job satisfaction among co-workers, likewise 36% indicated that plans, policies and strategies are implemented in a coordinated manner, on the other hand, 26% indicated that the designation of the positions and functions of the personnel are not in accordance with their professional profile, which has weakened their labor actions. It is concluded that there is a need to develop an improvement plan that helps to strengthen the weaknesses detected in the exploration, which was socialized with the relevant authorities of the institution and that will allow a positive change in decision-making for the benefit of all those involved into the entity.